Maintaining Vitality: Pharmacists’ Continuing Professional Education Decision-Making in the Upper Midwest - Henkel, Paul Jacob (Pharmacy (Basel), 2018)
Continuing professional education (CPE) plays an important role in continuing professional development of pharmacists for providing quality pharmaceutical care but also to maintain professional and organizational vitality and meet changing community/population needs. The study objective was to describe and understand factors of importance in selection of CPE credit hours among Upper Midwest pharmacists. A cross-sectional study of licensed pharmacists (n = 1239) in Iowa, Minnesota, Nebraska, North Dakota, and South Dakota included completion of a questionnaire on demographics and CPE decision-making. Factor analysis, t-test, and multivariate analyses were performed using Stata 10.1. Pharmacists placed greatest importance on maintaining licensure (mean = 2.72/3.00), personal interest (mean = 2.57), and self-improvement (mean = 2.42). Community/population need (mean = 1.83) was rated as slightly more important (p < 0.01) by retail/community pharmacists, females, and those with a Doctor of Pharmacy degree or pharmacy residency while business growth/development (mean = 1.33) was rated slightly more important (p < 0.01) by retail/community pharmacists. Despite findings that neither community/population need nor business development were among the most important factors in pharmacists’ CPE selection, there exists significant potential for pharmacists to utilize CPE to maintain professional and organizational vitality in the labor market, but more importantly to ensure continued provision of quality pharmaceutical care and patient education.